Morphological Characteristics Selection of Acid-tolerant Leucaena leucocephala Mutant to Addition of IBA Hormone (Indole butyric acid) in Tissue Culture - Panca Dewi Manuhara Karti; Mukhlisani Muhklisani; Iwan Prihantoro (Indonesian Center for Animal Research and Development (ICARD), 2022)
Leucaena leucocephala is a legume forage plant that has a high protein content. Tissue culture is a technique that can be used to select mutants for forage plants in vitro. IBA (Indole butyric acid) is one type of auxin that can induce rooting and growth in plants. This study aimed to select the morphological characteristics of the acid-tolerant Leucaena leucocephala mutant to the addition of the hormone IBA in tissue culture. The design used in this study was a completely randomized design (CRD) with lamtoro plant explants as many as 11 acid-tolerant mutant lines pH 3.4 resulting from 400 gy irradiation which had been treated on 300 ppm Al3+ acid media, namely the K1-K11 strain (mutant+MS+1ppm IBA) and 2 parent trees Leucaena leucocephala without gamma irradiation, namely P0 as Leucaena leucocephala parent+MS+0ppm IBA, P1 as Leucaena leucocephala parent + MS + 1 ppm IBA with 15 replicates. The treatment which had a significant effect was continued with the test Tukey. Variables observed were an increase in root length, plant vertical height, number of shoots, and percentage of rooted plants. The increase in root length and increase in plant vertical height showed the best results on the K10 mutant strain, the number of shoots showed the best results on the K9 and K11 mutant strains, and the highest percentage of rooted plants on the K3 and K11 mutant strains. The addition of IBA can increase the morphological characteristics of the Leucaena leucocephala mutant.